Activity and abundance of sulfate reducting bacteria and environmental parameter in serpentinizing fluids of Coast Range ophiolote (USA) and Samail ophiolote (Oman) - Glombitza, Clemens; Putman, Lindsay I; Rempfert, Kaitlin R; Kubo, Mike; Schrenk, Matthew O; Templeton, Alexis S; Hoehler, Tori M (PANGAEA, 2021)
We have measured microbial sulfate reduction rates by ultra sensitive radio tracer incubations in fluids from 11 wells of the actively serpentinizing the Coast Range ophiolite (CA, USA) and Samail ophiolite (Oman). We also determined environmental parameter of the serpentinizing fluids (pH, redox potential and chloride, sulfate, hydrogen, methane and organic acid conentrations. We also determiend the abundance of sulfate reducing taxa in the these fluids.
Keywords: ophiolites; radio-tracer; Serpentinization; Sulfate reducing bacteria abundance; sulfate reduction rates